PENGARUH MODEL CPS (CREATIVE PROBLEM SOLVING) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SD KELAS V SDN 98 PALEMBANG (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the CPS (Creative Problem Solving) learning model on students' problem solving abilities in Mathematics subjects of class V SD Negeri 98 Palembang. This study uses the Quantitative Non-Equivalent Control Group Design method. The independent variables in this study are the CPS (Creative Problem Solving) learning model and the dependent variable is students' mathematical problem solving abilities. The sample in this study used two classes selected using the Saturated Sampling Technique at SD Negeri 98 Palembang. The data analysis methods used in this study are Validity Test, Reliability Test, Normality Test, Homogeneity Test, and Intenpendent Sample T-Test. Data Processing Results Show the Average Posttest of the Experimental Class is 81.07 and the Control Class is 44.64. In Hypothesis Testing, t count> t table or 0.05> 000 is obtained, Based on the Independent Sample T-Test Test in this study, the Sig (2-Tailed) value is 0.000 <0.05, so it can be concluded that the significant value is smaller than 0.05, then Ho is rejected and Ha is accepted. Thus, there is a significant difference between classes using the CPS learning model and conventional learning models.